Puccinia psidii in Queensland, Australia: disease symptoms, distribution and impact. (11th December 2013) - Pegg, G. S.; Giblin, F. R.; McTaggart, A. R.; Guymer, G. P.; Taylor, H.; Ireland, K. B.; Shivas, R. G.; Perry, S.
<x xml:space="preserve">Abstract</x> Puccinia psidii has long been considered a significant threat to Australian plant industries and ecosystems. In April 2010, P. psidii was detected for the first time in Australia on the central coast of New South Wales (NSW). The fungus spread rapidly along the east coast and in December 2010 was found in Queensland (Qld) followed by Victoria a year later. Puccinia psidii was initially restricted to the southeastern part of Qld but spread as far north as Mossman. In Qld, 48 species of Myrtaceae are considered highly or extremely susceptible to the disease. The impact of P. psidii on individual trees and shrubs has ranged from minor leaf spots, foliage, stem and branch dieback to reduced fecundity. Tree death, as a result of repeated infection, has been recorded for Rhodomyrtus psidioides. Rust infection has also been recorded on flower buds, flowers and fruits of 28 host species. Morphological and molecular characteristics were used to confirm the identification of P. psidii from a range of Myrtaceae in Qld and compared with isolates from NSW and overseas. A reconstructed phylogeny based on the LSU and SSU regions of rDNA did not resolve the familial placement of P. psidii, but indicated that it does not belong to the Pucciniaceae. Uredo rangelii was found to be con‐specific with all isolates of P. psidii in morphology, ITS and LSU sequence data, and host range.